Application of simplicial technology in Haleu herbal tea production for enhancing body immunity [Aplikasi teknologi simplisia dalam produksi teh herbal Haleu untuk meningkatkan imunitas tubuh] - Sari, Irma; Elizar, E; Fajri, Nova; Susilawati, S; Marisa, M; Suryawatie, S (Universitas Syiah Kuala, 2025)
The use of family medicinal plants (Tanaman Obat Keluarga/TOGA) has long been an integral part of local wisdom, passed down through generations in various regions, including among the Family Welfare Empowerment (PKK) women's group in Cot Bada Village. While the group has extensive experience in cultivating medicinal plants, the downstream processing of these resources into value-added products remains suboptimal. This community service program aims to enhance the skills of the PKK women's group in Cot Bada Village, Aceh Besar, in processing lemongrass and ginger into a herbal tea product called Teh Haleu. Through training based on appropriate technology, participants were introduced to the tea production process, including selecting high-quality ingredients, drying using a Food dehydrator Tray, and packaging the product attractively to meet market standards. Additionally, financial management and marketing training was provided to support the sustainability of the business. The program's outcomes revealed that the PKK women successfully produced Teh Haleu ready for sale with high-quality standards, receiving positive feedback from the market. As a follow-up, plans include mass production and obtaining BPOM and halal certifications to enhance the product's competitiveness and economic potential. This program delivers economic benefits and empowers the community to optimize local resources effectively and sustainably.